Історія еколого-геохімічних досліджень ландшафтів Західного регіону України - Міщенко, Л. В.; Mishchenko, L. V. (Волин. нац. ун-т ім. Лесі Українки, 2012)
Розглянуто наукові напрями оцінки сучасної екологічної ситуації, історію їх розвитку у географічній науці, де перспективним, на наш погляд, є конструктивно-техноекологічний. We propose to discuss several methods of the modern ecological situation, the history of its development in the geographical science, among which the most effective is the constructive-technological branch.
The History of Ecological-Geochemical Exploring the Landscapes of Eastern Region of Ukraine.
Keywords: моніторинг; Карпатський регіон; екомоніторинг; екологічна ситуація; ландшафт; monitoring; Carpatian region; ecomonitoring; ecological situation; landscape